Expanding Pathology: Risk Reduction, Illicit Procedures, and Catholic Health Care - Berendes, Samuel (Christian bioethics, 2026)
The Catholic Church's rejection of direct sterilization and acceptance of indirect sterilization has led to complex dialogue on what separates the two. Central to Catholic thought's ability to parse the difference between direct and indirect sterilization is an understanding of pathology. Increasing data and literature on the pathogenesis of disease, both in terms of the specific risks associated with pregnancy as well as in the more general context of female reproductive health, complicate these questions. Given these findings, I argue that Church teaching on sterilization relies on an unnecessarily narrow standard of pathology. I rely on debate around risk-reducing salpingectomy and the application of these principles in the conditions surrounding placenta accreta spectrum and preeclampsia to articulate a broader understanding of pathology. I argue that pathology should account for the potentially pathological interaction between reproductive organs and other parts of the body. This expanded definition gives rise to potentially broader applications of indirect sterilization that could prove more responsive to a broader range of reproductive health risks.